Induction of resistance to Mycosphaerella fijiensis Morelet and its relationship with yield of banana plants (Musa AAA) CV. Williams - Terrero Yepez, Pedro Isaías (2020)
Bananas are widely grown in Ecuador, being the most exported crop, however, fruit production is reduced by phytosanitary diseases such as black Sigatoka. Management of this disease includes mostly chemical synthesis fungicides that contribute to environmental pollution.  For this reason, this experiment was carried out in the central zone of the ecuadorian coastal region, to evaluate at field level the effect of inducing resistance substances against the evolution of  “black Sigatoka” in the dry and rainy seasons. The experiment was deployed in a complete randomized block design, with five treatments and 4 blocks. The treatments studied were T1: Jasmonic acid, T2: Salicylic acid, T3: Carophilaceas extract, plus chemical (T4) and absolute (T5) controls. The infection rate, leaf area and functional leaves were measured at both, flowering and harvest stages. Additionally, net bunch weight was also evaluated. Jasmonic and salicylic acid showed a negative effect on the infection rate in both production periods. In terms of net bunch weight, Salicylic Acid registered the best average, compared to other treatments. Finally, this experiment showed that these resistance inducers can be implemented in disease management programs, as well as to increase crop yield, thus reducing the use of chemical products whose indiscriminate use creates resistance and environmental contamination.